La Unión Europea ante la democracia y los derechos humanos: entre los principios de la superpotencia civil y la defensa de los intereses - Sotillo Lorenzo, José Ángel (Revista Española de Desarrollo y Cooperación, 2023)
The European Union pretends to convey the image that their rationality and international conduct are based in democracy and human rights perspective. Thus, has been built a policy of promoting democracy and human rights linked to foreign affairs, which undoubtedly represents a major step toward the configuration of a democratic governance world. However there are no doubts that its declaratives profile is heavier than a coherent behaviour.